Efficient and stable CRISPR/Cas9-mediated genome-editing of human type 2 innate lymphoid cells - Audouze-Chaud, Johanne; Mathews, Jessica A.; Crome, Sarah Q. (Frontiers in Immunology, 2023)
Innate lymphoid cells (ILCs) are a family of innate lymphocytes with important roles in immune response coordination and maintenance of tissue homeostasis. The ILC family includes group 1 (ILC1s), group 2 (ILC2s) and group 3 (ILC3s) ‘helper’ ILCs, as well as cytotoxic Natural Killer (NK) cells. Study of helper ILCs in humans has several challenges, including their low proportions in peripheral blood or needing access to rare samples to study tissue resident ILC populations. In addition, the lack of established protocols harnessing genetic manipulation platforms has limited the ability to explore molecular mechanism regulating human helper ILC biology. CRISPR/Cas9 is an efficient genome-editing tool that enables the knockout of genes of interest, and is commonly used to study molecular regulation of many immune cell types. Here, we developed methods to efficiently knockout genes of interest in human ILC2s. We discuss challenges and lessons learned from our CRISPR/Cas9 gene editing optimizations using a nucleofection transfection approach and test a range of conditions and nucleofection settings to obtain a protocol that achieves effective and stable gene knockout while maintaining optimal cell viability. Using IL-4 as a representative target, we compare different ribonucleoprotein configurations, as well as assess effects of length of time in culture and other parameters that impact CRISPR/Cas9 transfection efficiency. Collectively, we detail a CRISPR/Cas9 protocol for efficient genetic knockout to aid in studying molecular mechanism regulating human ILC2s.